Microbiome Variation Across Two Hemlock Species With Hemlock Woolly Adelgid Infestation - Dove, Nicholas C.; Rogers, Timothy J.; Leppanen, Christy; Simberloff, Daniel; Fordyce, James A.; Brown, Veronica A.; LeBude, Anthony V.; Ranney, Thomas G.; Cregger, Melissa A. (Frontiers in Microbiology, 2020)
The hemlock woolly adelgid (Adelges tsugae, HWA), an invasive insect, is devastating native hemlock populations in eastern North America, and management outcomes have so far had limited success. While many plant microbiomes influence and even support plant immune responses to insect herbivory, relatively little is known about the hemlock microbiome and its interactions with pathogens or herbivores such as HWA. Using next-generation sequencing of the 16S rRNA and ITS gene regions, we characterized the needle, branch, root, and rhizosphere microbiome of two hemlock species, Tsuga canadensis and T. sieboldii, supporting low and high levels of HWA populations. We found that both archaeal/bacterial and fungal needle communities, as well as the archaeal/bacterial branch and root communities, varied in composition in both species relative to HWA population levels. Specifically, high HWA populations were associated with enrichment of 27 fungal pathogen sequence variants across the four plant-associated habitats (e.g., needle, branch, root, rhizosphere) compared to trees with low HWA populations. Host species and plant-associated habitat, however, explained a greater proportion of the variance in the microbiome than did HWA population level. Nevertheless, this work contributes to a growing body of literature linking plant pathogens and pests with the plant microbiome and host health and demonstrates the need to investigate plant microbiome effects across multiple plant tissues.